Development, mechanical characterization and analysis of dry sliding wear behavior of AA6082–Metakaolin metal matrix composites. (13th November 2019) - Bright, Renjin J; Selvakumar, G; Sumathi, M; Lenin, N
Abstract: This work emphasized the preparation, mechanical characterization, and evaluation of dry sliding wear behaviour of Aluminium Alloy (AA) 6082 metal matrix composites reinforced with metakaolin particles. The reinforcement particles were incorporated in the aluminium matrix at an amount of 0% to 15% in terms of weight, in a step of 2.5%. Ultra-sonic cavitation assisted stir casting process was employed for the preparation of the composites and the prepared composites were subjected to T6 heat treatment. Optical micrographs were utilized to examine the dispersion of reinforcement particles in the matrix. The tensile properties were enhanced with an increase in the amount of the reinforcement particles up to 7.5 weight % and then started to degrade. The micro-hardness and wear behaviour also expressed a similar trend. The fractured surfaces were examined using a Scanning Electron Microscope (SEM). The pin-on-disc wear test was employed to characterize the wear behaviour of the composites. Wear rate and average coefficient friction of the prepared composites were analyzed by varying the significant parameters such as load, sliding velocity, and sliding distance. Field emission scanning electron microscope (FESEM) and energy dispersive spectroscopy (EDS) data were utilized to examine the worn-out surfaces. The T6 heat-treated specimens expressed remarkable enhancement in mechanical and wear properties compared to as-cast samples.